Pseudoaneurysm and aorto-bronchial fistula following balloon dilation of recoarctation. (11th September 2015) - Sinelnikov, Yuri S.; Kornilov, Igor A.; Soynov, Ilya A.
Abstract: This case report documents the successful surgical repair of an aorto-bronchial fistula and a giant aortic pseudoaneurysm at the proximal anastomosis of a dacron interposition tube graft that was balloon dilated for recurrent coarctation. Balloon dilation for recoarctation of a dacron interposition tube graft may lead to serious complications.